PENGARUH DISIPLIN BELAJAR DAN KREATIVITAS GURU TERHADAP PRESTASI BELAJAR MATA PELAJARAN IPS SISWA DI SMK BATIK 1 SURAKARTA - Ainun Nur Aini; Dewi Kusuma Wardani; Jonet Ariyanto Nugroho (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
This research is aimed to know: (1) the effect of the learning discipline and the teacher’s creativity towards the students’ learning achievement in the Social subject in SMK Batik 1 Surakarta; (2) the effect of the learning discipline towards the students’ learning achievement in the Social subject in SMK Batik 1 Surakarta; (3) the effect of the teacher’s creativity towards the students’ learning achievement in the Social subject in SMK Batik 1 Surakarta.This research is a descriptive study with quantitative method. The population of this research is all of the students from XI class of SMK Batik 1 Surakarta, consisted of 246 students. The sample chosen was consisted of 146 students by using Proportional Random Sampling as the technique of sampling. Try out was conducted for 30 respondents out of the main sample. The technique of collecting the data was using questionnaire. The technique of analyzing the data used in this research was double linier regression.Based on the result of the research, it can be conclude that: (1) there is an effect of of the learning discipline and the teacher’s creativity towards the students’ learning achievement as shown by the score of Fstatistic >Ftable; 293,499 > 3,060. (2) there is a significant effect of the learning discipline towards the students’ learning achievement as shon by the score of t statistic>t table; 7,368 > 1,977. (3) there is a significant effect of the teacher’s creativity towards the students’ learning achievement as shown by the score of t statistic>t table; 19,759 > 1,977. The coefficient of determination is 72,5%, this shows that 72,5% of the students’ learning achievement is affected by the students’ learning discipline and the teacher’s creativity, meanwhile the rests of 27,5% is affected by the other factors which are not explained in the research.